Association of CHA2DS2-VASc Score with Post Cardiac Surgery Atrial Fibrillation: A Single Centre Study - Alam, Waqas; Hussain, Syed Aqeel; Masroor, Rehan; Hasan Kirmani, Syed Muzaffar; Ali, Muhammad; Rehman, Fahd Ur; Javaid, Rehana; Khalil, Hafsa (Pakistan Armed Forces Medical Journal, 2022)
Objective: To find out the association of CHA2DS2-VASc score with postoperative atrial fibrillation in cardiac surgery patients. Study Design: Analytical Cross-Sectional study. Place and Duration of Study: Cardiothoracic Anaesthesia and Adult Cardiac Critical Care department, Armed Forces Institute of Cardiology and National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi Pakistan, from Feb 2022 to Apr 2022. Methodology: After IERB approval, 186 adult patients of POAF with the prevalence of 9.7%undergoing CABG surgery were included in the study. Their demographic data and CHA2DS2-VASc score, originally used to find the risk of stroke in patients with atrial fibrillation, was calculated pre-operatively. They were followed for 48 hours postoperatively for any episode of post op atrial fibrillation (POAF). Data including pre op drugs, type of surgery, number of grafts, inotropic support and POAF timing after surgery was recorded and analysed by SPSS v 21.0. Results: Incidence of POAF in our study patients was 17.2 %( n=32). Mean time of onset of POAF was 24.75±16.05 hours.Patients who developed POAF had higher CHA2DS2-VASc score 3.06±1.21 compared with those who did not develop POAF 2.61±0.97. This association was statistically significant (p-value=0.023). Among the variables of CHA2DS2-VASc score, age had significant association with POAF (p-value= 0.001). No difference was found between on pump vs off pump surgery in terms of POAF (p-value=0.539). Conclusion: This study found that CHA2DS2-VASc score has significant association with POAF after CABG surgery. It is a simple and easy scoring system which can be calculated in preoperative period. Patients at increased risk of POAF can be identified and given prophylactic treatment to reduce morbidity and mortality.